The species of the bee genus Centris Fabricius (Hymenoptera: Apidae) described by Giovanni Gribodo - Felipe Vivallo (Revista Chilena de Entomología, 2020)
In this paper the prima ry types of Centris bees described by the Italian entomologist Giovanni Gribodo were studied. The type specimens of C. citrotaeniata, C. deiopeia, C. denudans var. rubida, C. proserpina, C. quartinae, Anthophora plumigera, and A. virgo were analyzed, providing notes on their current status and depository. To stabilize the application of the name C. citrotaeniata it was designating a lectotype for the species. Notes and photographs of the primary types are also provided.